Tingkat Kecemasan Siswa Dalam Menghadapi Ujian Nasional Berbasis Komputer (UNBK) di SMK Al Munawwariyyah Bululawang - Tyas Andriansyah; Eva Kartika Wulan Sari (JKI (Jurnal Konseling Indonesia), 2017)
The high anxiety level of students when facing the National Exam Computer-Based (UNBN ) caused the negative effect. Which come from the internal and external factor. The formulation of the problem is how much anxiety level of students when facing the UNBK, the purpose of this study is to know the anxiety of students when facing UNBK. The respondents are 44 students from grade 12 the majority of Computer and network technic year 2015-2016. The result of the research showed 7% of the students has low level of anxiety, 77% of the students have an average level of anxiety and 16% of the students have high level of anxiety. Variably, level of anxiety divided into 3 they are realistic anxiety, neurotic anxiety and moral anxiety. The result based on the sub variable is the reality anxiety showed 16% of students in the low level, 59% in average level and 25% in high level. While the neurotic anxiety showed 2% in low level, 59% in average level and 25% in high level. The last, morality anxiety showed 27% in low level, 61% in average level and 11% in high level.